SURVEI SARANA DAN PRASARANA PENJASORKES DI SMP NEGERI SE- KECAMATAN PURWAREJA KLAMPOK KABUPATEN BANJARNEGARA TAHUN AJARAN 2012/ 2013 (Department of Physical Education, Sport, Health and Recreation, 2015)
This research intent to know condition of medium and prasarana is sport and health physical education at SMP Country one Purwareja Klampok's district Banjarnegara's Regency school year 2012 / 2013. Method that is utilized in this research is quantitative. Approaching that is utilized gets analisis's descriptive character. This observational type is observational survey. This observational population is all SMP Country One Purwareja Klampok's district that total 3 schools . Sample took by samplings totaled tech and result sample as much 3 SMP. Methodic data collecting that digunkan is methodic questionnaire or kuesioner, observation method, method documents, and interview's method. Base observational result to be known that medium average and prasarana for branch sporting athletic with presentase 65.04%, basketball (44.00%), football (54.76%), for volleyball (53.57%), badminton (73.91%), gymnastics (50.00%), school health (55.34%).Of research and study result gets to be concluded that medium and prasarana penjasorkes at SMP Country One Purwareja Klampok's district Banjarnegara's regency adequately is equal to Penjasorkes's learning.